A World View of Maya in Raja Ampat Kingdom Mythology in West Papua - Insum Malawat; Hengki Mofu; Akhiruddin; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2022)
Myth in Maya ethnic, West Papua, Indonesia is an old story contained truth element that is truly believed as a story that ever happened in the past time because it is supported by inheritance culture feature in society. Myth is a source of important information used to dig and understand the way of local people think which is combined and facilitate in the form of verbal narrative. Raja Ampat kingdom Mythology talks about the origin of Raja Ampat name and Maya ancestor as well which is believed comes from Maleo bird egg. This story is considered as a holy story by the owner and it preserves in Kali Raja ritual in South Waigeo. This ritual is done annually with the purpose of cleaning and changing “cloth” of king’s stone or seventh ancestor of Maya that has aleready become a stone and chooses to live at the place where they ancestors were born that is Kali Raja. The belief of the truth of the element of Maya story can be seen from the dancer and ritual actor as well. This writing used verbal literature of sociology. The source of the data is the script document of Raja Ampat myth with an object of this study is the viewpoint of live and worldview.